SPONTANEOUS CARPAL TARSAL OSTEOLYSIS IN CHILDREN'S RHEUMATOLOGIST PRACTICE - E.S. Zholobova; V.N. Bobyleva; G.V. Mikhaleva ("Paediatrician" Publishers LLC, 2008)
The case report of spontaneous carpalbtarsal osteolysis in 11byearbold boy is presented in this article. The attention draw to the rarity of this disease, the literature data of spontaneous osteolysis was given. The features of clinical presentation were described, and need of differential diagnosis with juvenile rheumatoid arthritis was proved. Key words: spontaneous carpal tarsal osteolysis, differential diagnosis.